Oral Ingestion of Bean Sprouts Containing the HASPIN Inhibitor Coumestrol Increased Blood Testosterone Levels in Men - Keisuke Kakazu (Biology, 2025)
Extending healthy lifespans is an important public health goal in societies with a long life expectancy. Late-onset hypogonadism (LOH), a condition associated with an age-related decrease in testosterone level, contributes to the onset of various diseases. Previously, we demonstrated that the oral ingestion of bean sprouts rich in the HASPIN inhibitor coumestrol increased blood testosterone levels in mice. In the present study, we showed that the oral ingestion of bean sprouts also led to increased blood testosterone levels in humans. These results suggested that bean sprouts, which are rich in coumestrol, have potential as a dietary intervention for the treatment of LOH.